A qualitative study to explore healthcare providers' perspectives on barriers and enablers to early detection of breast and cervical cancers among women attending primary healthcare clinics in Johannesburg, South Africa. - Gugulethu Tshabalala; Charmaine Blanchard; Keletso Mmoledi; Desiree Malope; Daniel S O'Neil; Shane A Norris; Maureen Joffe; Janan Janine Dietrich (PLOS Global Public Health)
Low-and-middle income countries (LMICs) contribute approximately 70% of global cancer deaths, and the cancer incidence in these countries is rapidly increasing. Sub-Saharan African (SSA) countries, including South Africa (SA), bear some of the world's highest cancer case fatality rates, largely attributed to late diagnosis. We explored contextual enablers and barriers for early detection of breast and cervical cancers according to facility managers and clinical staff at primary healthcare clinics in the Soweto neighbourhood of Johannesburg, South Africa. We conducted qualitative in-depth interviews (IDIs) between August and November 2021 amongst 13 healthcare provider nurses and doctors as well as 9 facility managers at eight public healthcare clinics in Johannesburg. IDIs were audio-recorded, transcribed verbatim, and entered into NVIVO for framework data analysis. Analysis was stratified by healthcare provider role and identified apriori around the themes of barriers and facilitators for early detection and management of breast and cervical cancers. Findings were conceptualised within the socioecological model and then explored within the capability, opportunity and motivation model of behaviour (COM-B) for pathways that potentially influence the low screening provision and uptake. The findings revealed provider perceptions of insufficient South African Department of Health (SA DOH) training support and staff rotations resulting in providers lacking knowledge and skills on cancer, screening policies and techniques. This coupled with provider perceptions of poor patient cancer and screening knowledge revealed low capacity for cancer screening. Providers also perceived opportunity for cancer screening to be undermined by the limited screening services mandated by the SA DOH, insufficient providers, inadequate facilities, supplies and barriers to accessing laboratory results. Providers perceived women to prefer to self-medicate and consult with traditional healers and access primary care for curative services only. These findings compound the low opportunity to provide and demand cancer screening services. And because the National SA Health Department is perceived by providers not to prioritize cancer nor involve primary care stakeholders in policy and performance indicator development, overworked, unwelcoming providers have little motivation to learn screening skills and provide screening services. Providers reported that patients preferred to go elsewhere and that women perceived cervical cancer screening as painful. These perceptions must be confirmed for veracity among policy and patient stakeholders. Nevertheless, cost-effective interventions can be implemented to address these perceived barriers including multistakeholder education, mobile and tent screening facilities and using existing community fieldworkers and NGO partners in providing screening services. Our results revealed provider perspectives of complex barriers to the early detection and management of breast and cervical cancers in primary health clinic settings in Greater Soweto. These barriers together appear potentially to produce compounding effects, and therefore there is a need to research the cumulative impact but also engage with stakeholder groups to verify findings and create awareness. Additionally, opportunities do exist to intervene across the cancer care continuum in South Africa to address these barriers by improving the quality and volume of provider cancer screening services, and in turn, increasing the community demand and uptake for these services.